Optimal growth temperature of Arctic soil bacterial communities increases under experimental warming - Rijkers, Ruud; Rousk, Johannes; Aerts, Rien; Sigurdsson, Bjarni D.; Weedon, James T. (Global Change Biology, 2022)
Future climate warming in the Arctic will likely increase the vulnerability of soil carbon stocks to microbial decomposition. However, it remains uncertain to what extent decomposition rates will change in a warmer Arctic, because extended soil warming could induce temperature adaptation of bacterial communities. Here we show that experimental warming induces shifts in the temperature–growth relationships of bacterial communities, which is driven by community turnover and is common across a diverse set of 8 (sub) Arctic soils. The optimal growth temperature (Topt) of the soil bacterial communities increased 0.27 ± 0.039 (SE) and 0.07 ± 0.028°C per °C of warming over a 0–30°C gradient, depending on the sampling moment. We identify a potential role for substrate depletion and time-lag effects as drivers of temperature adaption in soil bacterial communities, which possibly explain discrepancies between earlier incubation and field studies. The changes in Topt were accompanied by species-level shifts in bacterial community composition, which were mostly soil specific. Despite the clear physiological responses to warming, there was no evidence for a common set of temperature-responsive bacterial amplicon sequence variants. This implies that community composition data without accompanying physiological measurements may have limited utility for the identification of (potential) temperature adaption of soil bacterial communities in the Arctic. Since bacterial communities in Arctic soils are likely to adapt to increasing soil temperature under future climate change, this adaptation to higher temperature should be implemented in soil organic carbon modeling for accurate predictions of the dynamics of Arctic soil carbon stocks.